Raman detection of a peroxy intermediate in the hydroquinone-oxidizing cytochrome aa3, of Bacillus subtilis - Babcock, Gerald T.; Lauraeus, Marko; Varotsis, Constantinos (My University, 1995)
When the mixed valence, carbon monoxide-bound form of the hydroquinone-oxidizing cytochrome aa3-600 of Bacillus subtilis is illuminated in the presence of O2, it forms a species that corresponds to 'Compound C', first described for the mitochondrial cytochrome c oxidase by Chance, Saronio and Leigh (J. Biol. Chem. 250 (1975) 9226-9237). Resonance Raman spectra of the this species show a mode at 366 cm-1 that shifts to 342 cm-1 when the experiment is repeated with 18O2. The appearance of this mode is insensitive to deuteration exchange within the limits of resolution. High- (1200-1700 cm-1) and low-frequency (200-500 cm-1) data, allow us to assign the 366 cm-1 mode to the Fe3+-O stretching vibration of a peroxide adduct where the iron is either low or intermediate spin. This is to our knowledge the first time an 18O2-sensitive iron-oxygen stretching mode has been reported for 'Compound C', providing strong support for the notion that this species is a peroxide adduct. The observed 366 cm-1 υ(Fe3+-O--O-) frequency is 8 cm-1 higher than that previously found for a transient peroxy intermediate in the reaction between the fully reduced mitochondrial enzyme and O2. Our observation indicates that, while similar, the metastable peroxyheme a3 species reported here differs in the fine details of geometry, protonation state, and/or hydrogen bond status
Keywords: Raman spectroscopy; Cytochrome oxidase; Bacillus subtilis; Enzymes; Peroxides